Dystrophic changes in extraocular muscles after gamma irradiation in mdx:utrophin(+/-) mice. - Abby A McDonald (Public Library of Science (PLoS), 2014)
Extraocular muscles (EOM) have a strikingly different disease profile than limb skeletal muscles. It has long been known that they are spared in Duchenne (DMD) and other forms of muscular dystrophy. Despite many studies, the cause for this sparing is not understood. We have proposed that differences in myogenic precursor cell properties in EOM maintain normal morphology over the lifetime of individuals with DMD due to either greater proliferative potential or greater resistance to injury. This hypothesis was tested by exposing wild type and mdx:utrophin(+/-) (het) mouse EOM and limb skeletal muscles to 18 Gy gamma irradiation, a dose known to inhibit satellite cell proliferation in limb muscles. As expected, over time het limb skeletal muscles displayed reduced central nucleation mirrored by a reduction in Pax7-positive cells, demonstrating a significant loss in regenerative potential. In contrast, in the first month post-irradiation in the het EOM, myofiber cross-sectional areas first decreased, then increased, but ultimately returned to normal compared to non-irradiated het EOM. Central nucleation significantly increased in the first post-irradiation month, resembling the dystrophic limb phenotype. This correlated with decreased EECD34 stem cells and a concomitant increase and subsequent return to normalcy of both Pax7 and Pitx2-positive cell density. By two months, normal het EOM morphology returned. It appears that irradiation disrupts the normal method of EOM remodeling, which react paradoxically to produce increased numbers of myogenic precursor cells. This suggests that the EOM contain myogenic precursor cell types resistant to 18 Gy gamma irradiation, allowing return to normal morphology 2 months post-irradiation. This supports our hypothesis that ongoing proliferation of specialized regenerative populations in the het EOM actively maintains normal EOM morphology in DMD. Ongoing studies are working to define the differences in the myogenic precursor cells in EOM as well as the cellular milieu in which they reside.